2020
DOI: 10.3390/nano10091743
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and Anti-Inflammatory Behavior of Injectable Calcium Phosphate Loaded with Therapeutic Drugs

Abstract: Bone fractures related to musculoskeletal disorders determine long-term disability in older people with a consequent significant economic burden. The recovery of pathologically impaired tissue architecture allows avoiding bone loss-derived consequences such as bone height reduction, deterioration of bone structure, inflamed bone pain, and high mortality for thighbone fractures. Actually, standard therapy for osteoporosis treatment is based on the systemic administration of biphosphonates and anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Nanocarriers of different composition have also been studied for the delivery of DF for biomedical applications, such as polysaccharides [ 63 ], poly(ε-caprolactone) micelles [ 64 , 65 ], magnetic NPs [ 66 ]. Concerning the adsorption of DF on any form of apatite as adsorbent, it was recently reported the adsorption on amino hydroxyapatite/chitosan/glutaraldehyde hybrids composites at pH 6 [ 67 ], and the release of DF from injectable CaP-loaded systems to treat inflammation [ 68 ], but these authors did not study the adsorption isotherms, nor used luminescent apatites, therefore we cannot compare our results. In line with what we reported here (see beyond), in all these cases the compositions showed an anti-inflammatory activity on inflammation in vitro and in vivo experimental models.…”
Section: Discussionmentioning
confidence: 96%
“…Nanocarriers of different composition have also been studied for the delivery of DF for biomedical applications, such as polysaccharides [ 63 ], poly(ε-caprolactone) micelles [ 64 , 65 ], magnetic NPs [ 66 ]. Concerning the adsorption of DF on any form of apatite as adsorbent, it was recently reported the adsorption on amino hydroxyapatite/chitosan/glutaraldehyde hybrids composites at pH 6 [ 67 ], and the release of DF from injectable CaP-loaded systems to treat inflammation [ 68 ], but these authors did not study the adsorption isotherms, nor used luminescent apatites, therefore we cannot compare our results. In line with what we reported here (see beyond), in all these cases the compositions showed an anti-inflammatory activity on inflammation in vitro and in vivo experimental models.…”
Section: Discussionmentioning
confidence: 96%
“…With the incorporation of drugs multi-target therapy is possible – incorporated drugs can be able to not only treat inflammation, but also inhibit bone degeneration [ 192 ]. Farbod et al showed that sustained release drugs can also be engineered.…”
Section: Injectable Calcium Phosphates As Drug Delivery Systemsmentioning
confidence: 99%
“…It is great for aching muscles and stiff joints in women who suffer from menopause symptoms in their joints and muscles. 73,74…”
Section: Harpagophytum Procumbens (Devil's Claw)mentioning
confidence: 99%